Catholics and Politics: The Dynamic Tension between Faith and Power - Cochran, David Carroll (A journal of church and state, 2009)
Exploring the relationship of Catholicism and American politics raises both normative and empirical questions. On the normative side are those who ask what role the Catholic tradition should play in American public life, or how Catholics should allow their faith to guide their political decisions. On the empirical side are those who ask what actual impact Catholic leaders, voters, or office holders have on the American political system, or in what ways, if any, Catholics are politically distinctive. One of the real strengths of this excellent volume is how it engages both kinds of questions.